The Use of Audio Visual Media In Improving The Quality Of PAI Learning In SMA Negeri City Of Bandung - Neneng Maemunah; Iim Wasliman; Deti Rostini; Sayid Muhammad Rifky Naufal (Journal of Social Science, 2021)
The background of the research is based on basic problems including audio-visual learning media as a support for the learning process in the world of education that is not optimal, lack of human resources and rapid technological developments, the readiness of the world of education itself must be able to balance and harmonize the system in optimizing the process of educational activities. The general purpose of this research is to find an overview of Computer-Based Learning Management in Improving the Quality of Student Learning Outcomes. The focus of the objectives is specifically to seek an overview: 1) Planning; 2) Organizing; 3) Implementation; 4) Supervision; 5) Problems; 6) Future Efforts; and 7 Results of Audio Visual Learning Media in Improving the Quality of PAI learning. Audio Visual Learning Media Theory is the basis of this research. The research procedure is determined by the determination of qualitative methods, through the process of: 1) Observation; 2) Interview; 3) Documentation. Which is developed through the triangulation process. The findings of the study of Audio Visual Learning Media Management in Improving the Quality of PAI Learning. Includes the process 1) Planning, its implementation in accordance with the development of computer-based learning is still within the scope of the process as the implementation of educational activities and has not been developed in full planning to support student learning outcomes; 2) Organizing, showing that the pattern of supporting human resources in the proportion of audio-visual learning media development is not in line with the developments currently needed. 3) Implementation, operation of audio-visual learning media only builds competence for the introduction of Information and Communication Technology in general without being developed with the application of the system in the educational environment itself 4) Supervision, specifically in building computer-based learning systems, mechanisms for implementing computer systems have not yet been built themselves in building student learning outcomes. 5) Problems, the readiness of Human Resources, facilities and systems for computer-based learning mechanisms themselves have not been developed; 6) Future Efforts, waiting for the policy to become the basis for determining the operational form in building a computer-based learning process unit and 7) Results, which are the consequences of the pattern of supporting infrastructure facilities that are needed with a balance of supporting human resources in it and this has not been built in unit for implementing educational activities at the Research locus. In conclusion, optimizing the form of application of the use of audio-visual media in improving the quality of PAI learning. Students are needed in building the quality of student learning outcomes where information is developed through broad literacy development supported by balanced skills in utilizing and developing computer-based learning systems so that knowledge is built in developing knowledge. itself and the technology in it.